Impact of COVID-19 infection on lung function and nutritional status amongst individuals with cystic fibrosis: A global cohort study - Semenchuk, Julie; Naito, Yumi; Charman, Susan C.; Carr, Siobhán B.; Cheng, Stephanie Y.; Marshall, Bruce C.; Faro, Albert; Elbert, Alexander; Gutierrez, Hector H.; Goss, Christopher H.; Karadag, Bulent; Burgel, Pierre Régis; et al. (Journal of Cystic Fibrosis, 2024)
Background: Factors associated with severe COVID-19 infection have been identified; however, the impact of infection on longer-term outcomes is unclear. The objective of this study was to examine the impact of COVID-19 infection on the trajectory of lung function and nutritional status in people with cystic fibrosis (pwCF). Methods: This is a retrospective global cohort study of pwCF who had confirmed COVID-19 infection diagnosed between January 1, 2020 and December 31, 2021. Forced expiratory volume in one second percent predicted (ppFEV1) and body mass index (BMI) twelve months prior to and following a diagnosis of COVID-19 were recorded. Change in mean ppFEV1 and BMI were compared using a t-test. A linear mixed-effects model was used to estimate change over time and to compare the rate of change before and after infection. Results: A total of 6,500 cases of COVID-19 in pwCF from 33 countries were included for analysis. The mean difference in ppFEV1 pre- and post-infection was 1.4 %, (95 % CI 1.1, 1.7). In those not on modulators, the difference in rate of change pre- and post-infection was 1.34 %, (95 % CI -0.88, 3.56) per year (p = 0.24) and -0.74 % (-1.89, 0.41) per year (p = 0.21) for those on elexacaftor/tezacaftor/ivacaftor. No clinically significant change was noted in BMI or BMI percentile before and after COVID-19 infection. Conclusions: No clinically meaningful impact on lung function and BMI trajectory in the year following infection with COVID-19 was identified. This work highlights the ability of the global CF community to unify and address critical issues facing pwCF.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Coronavirus; COVID-19; Cystic fibrosis